2016
DOI: 10.1016/j.jenvman.2016.04.053
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of regional and national values for recovering threatened and endangered marine species in the United States

Abstract: It is generally acknowledged that willingness-to-pay (WTP) estimates for environmental goods exhibit some degree of spatial variation. In a policy context, spatial variation in threatened and endangered species values is important to understand, as the benefit stream from policies affecting threatened and endangered species may vary locally, regionally, or among certain population segments. In this paper we present WTP estimates for eight different threatened and endangered marine species estimated from a stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Our sample was allocated to the strata in proportion to each stratum's population characteristics, such as age, income, and gender, resulting in 22 to 230 households being assigned to each stratum. For example, the numbers of surveys allocated to households in Seoul, Busan, Daegu, Incheon Gwangju, Daejeon, Ulsan, Gyunggi, Gangwon, Chungbuk, Chungnam, Jeounbuk, Jeounnam, Gyungbuk, and Gyungnaum were 197, 71, 50, 55, 30,32,22,230,33,33,45,38,39,58, and 67, respectively. A random sampling was implemented within each stratum.…”
Section: Survey Method Sampling and CV Survey Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample was allocated to the strata in proportion to each stratum's population characteristics, such as age, income, and gender, resulting in 22 to 230 households being assigned to each stratum. For example, the numbers of surveys allocated to households in Seoul, Busan, Daegu, Incheon Gwangju, Daejeon, Ulsan, Gyunggi, Gangwon, Chungbuk, Chungnam, Jeounbuk, Jeounnam, Gyungbuk, and Gyungnaum were 197, 71, 50, 55, 30,32,22,230,33,33,45,38,39,58, and 67, respectively. A random sampling was implemented within each stratum.…”
Section: Survey Method Sampling and CV Survey Instrumentmentioning
confidence: 99%
“…Bosetti and Pearce [6] carried out a CV survey to estimate WTP for recreational use of seals and found that the mean WTP estimates for seeing seals recovered from an accident in a specialized sanctuary and seeing seals in the wild are GBP 8 and 9 per person, respectively. The mean annual WTP values for recovering humpback whale (Megaptera novaeangliae) and southern resident killer whale (Orcinus orca) in the United States were estimated to be USD 60.98 and 84.38 per household per year, respectively [22].…”
Section: A Brief Review Of the Literaturementioning
confidence: 99%
“…Ocean conditions resulting from climate forcing are the primary drivers of fisheries harvest variability within the CCE (Sherman, 2006). The many fishery species annually harvested within the CCE have socioeconomic-importance to the adjacent coastal communities (Fuller et al, 2017;Miller et al, 2017;Ritzman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CEM can better solve the problem of comparing profit and loss between the multiple attributes of ecosystem services, and it can reveal public preferences for each eco-functional attribute of ecosystem services [34]. Thus, CEM has been widely used for non-market valuation, including species conservation [35][36][37][38][39], wetland recovery [40][41][42][43][44], ecotourism preferences [45][46][47][48][49][50], tourists' preferences for land, the environmental functions of national parks [21,[39][40][41]51,52], and the exploration of methods for altering specific ecosystem services to affect economic benefits [34,[53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%